Ultraviolet Stimulated Emission from Sol-Gel Spin Coated ZnO Thin Films - Ahmed S. Razeen; A.-S. Gadallah; M. M. El-Nahass (Advances in Materials Science and Engineering)
Low cost ultraviolet stimulated emission has been generated using optical excitation of ZnO thin films deposited by sol-gel spin coating on n+ As-doped 100 Si-substrate. The number of deposited layers and the heat treatment have been investigated to obtain a film that can generate stimulated emission under optical excitation. The optimum condition for preparation of the film has been presented. X-ray diffraction and scanning electron microscope have been used for structural and morphological investigations. Input-output intensity dependence and spectral width, peak emission wavelength, and the quantum efficiency versus the pump intensity have been presented. A quantum efficiency of about 24.2% has been reported, a power exponent higher than 8 has been obtained in input-output intensity dependence, and a threshold of about 23 Mw/cm2 has been evaluated for the samples. The mechanism by which stimulated emission occurs has been discussed. The results show that sol-gel spin coating is a promising method for generating ultraviolet stimulated emission from ZnO thin films.